Diffraktive Optiken im Automobil - Achromatisierung, Athermalisierung, Formung von Scheinwerferlichtverteilungen - Schöne, Michael (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2017)
The complexity of optical systems in headlamps is increasing rapidly. This leads to new design concepts, but it is also leading to increasing influence of aberrations. This work is dealing with the minimization of chromatical and thermal effects by using diffractive optics. Therefore, a new lens design in combination with the optical simulation of diffractive structures based on ray tracing is presented.